Melacak Domestikasi Perempuan dalam RUU Ketahanan Keluarga Perspektif Hukum Islam - Mohsi, Mohsi (AN NUR: Jurnal Studi Islam, 2023)
This research focuses on the Family Resilience Bill. Family resilience has become urgent amidst the many family problems, both internal and external. In principle, the Family Resilience Bill aims to ensure a good family life by religious, ethical and statutory standards. However, not all of the contents of the Family Resilience Bill have positive implications, some articles tend to revive patriarchal forms of the family, such as the tendency to domesticate women. This research uses a literature study approach with normative legal research, the Family Resilience Bill as a primary source, and other laws as secondary sources, while also relying on academic texts, such as gender-related journals and books. The research results show that the concept of family in Islamic law envisions an egalitarian and reciprocal family system. Meanwhile, the Family Resilience Bill, even though it contains goodness to maintain the state system. However, apart from that, it contains articles that tend to and have the potential to domesticate women's role, which is legally regulated in the Human Rights Law regarding the equal rights and obligations of husband and wife.